COMPARISON OF INTRAVITREAL TRIAMCINOLONE ACETONIDE VERSUS INTRAVITREAL BEVACIZUMAB AS THE PRIMARY TREATMENT OF CLINICALLY SIGNIFICANT MACULAR EDEMA. Issue 2 (February 2015) - Liu, Qingyun; Hu, Yijun; Yu, Honghua; Yuan, Ling; Hu, Jie; Atik, Alp; Guan, Meng; Li, Dongli; Li, Xin; Tang, Shibo
Abstract : Objectives: To evaluate the short-term efficacy of triamcinolone acetonide versus bevacizumab for the treatment of diabetic, clinically significant, macular edema with different optical coherence tomography findings. Methods: Fifty eyes of 45 consecutive patients with diabetic, clinically significant, macular edema were incorporated in this prospective interventional case series. Patients were divided into 3 groups according to findings on optical coherence tomography: 1) macular edema combined with serous retinal detachment (Group 1), 2) diffused macular thickening (Group 2), and 3) cystoid macular edema (Group 3). Patients from each group were treated with a single intravitreal injection of triamcinolone (IVTA) or 2 intravitreal injections of bevacizumab (IVB) with an interval of 6 weeks. Patients were observed at 6, 12, and 24 weeks after IVTA or the first IVB injection. Best-corrected visual acuity (BCVA) and central retinal thickness (CRT) were examined at each visit. Repeated-measures analysis of variance was used to compare the efficacy of the treatment groups. Results: In Group 1, IVTA showed more favorable effects on CRT reduction and BCVA improvement compared with IVB at 6, 12, and 24 weeks ( P = 0.002, 0.001, 0.027 and P = 0.036, 0.001, 0.027), respectively. In Group 2, IVB had more CRT reduction than IVTA at 6 and 12 weeks ( P = 0.013 and 0.036), although there was no significant difference in BCVA improvement between the 2 groups ( P > 0.05). In Group 3, IVTA and IVB did not have significant effects on CRT reduction and BCVA improvement ( P > 0.05). Conclusion: The short-term efficacy of IVTA and IVB on treating clinically significant macular edema varied with different optical coherence tomography findings. In clinically significant macular edema combined with serous retinal detachment, IVTA may be more favorable than IVB in CRT reduction and BCVA improvement. In patients with diffused macular thickening, IVB may be better than IVTA in macular thickness reduction, although this does not translate to a significant improvement in BCVA. Abstract : The authors investigated the short-term efficacy of triamcinolone acetonide versus bevacizumab for the treatment of clinically significant macular edema stratified according to optical coherence tomography findings. Triamcinolone acetonide may be more favorable than bevacizumab in central retinal thickness reduction and visual acuity improvement in clinically significant macular edema combined with serous retinal detachment.